Tips and tricks in fetal echocardiography - Singh, Kuldeep (Jaypee Brothers Medical Publishers, 2014)
Easy to use reference providing physicians and sonographers with useful tips on how best to perform a foetal echocardiograph, allowing them to accurately evaluate normal and abnormal heart beat.